Knowledge, attitude, and practice among healthcare professionals of adverse drug reactions reporting in a tertiary care center - Dharmadhikari, Pranita P.; Date, Amit P.; Patil, Kartik S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: There has been a rapid increase in the number of drugs entering the market from last few decades. Preclinical and clinical data are insufficient to conclude the complete safety of drugs. Hence, it is necessary to have a robust pharmacovigilance system in place to generate safety signals. Under reporting of adverse drug reactions (ADRs) exists as an inherent weakness of current voluntary reporting scheme. This study was therefore taken up, to evaluate the knowledge, attitude, and practice about ADR reporting among doctors in a tertiary care center. Methods: The present study was a cross-sectional questionnaire-based study, which included prescribers of a tertiary care teaching hospital. We tried to find out the possible ways to improve reporting of ADR and factors responsible for deficient reporting of ADRs. Results: After analyzing the data, we observed that 59% of the responders were aware of the ADRs reporting system. And the most encouraging finding was 94% of the respondents think that this reporting system is necessary. However, the practice was very poor just 14% among the respondents. 74% and 61% of participants felt creating awareness among healthcare professionals, and training to healthcare professionals would lead to improvement in reporting of ADRs respectively. Main factors which discouraged ADR reporting by healthcare professionals were reporting would lead to extra work 70.5%, non-availability of forms 64.5%. Conclusion: The deficiencies in ADR reporting require attention so as to improve spontaneous reporting and enhance safety of patients.